The Decolonisation of Climate Change and Environmental Education in Africa - Mbah, Marcellus Forh; Ezegwu, Chidi (Sustainability, 2024)
This study examines key considerations for the decolonisation of climate change and environmental education (CCEE) in Africa. It draws on insights into epistemic inclusivity to systematically assess journal articles that drew on primary studies and were published between 2015 and 2022. The findings of the review depict that there are persistent epistemic exclusion and alienation of Indigenous and local knowledge (ILK) in CCEE. This lack of recognition of ILK contributes to negatively affecting the quality of what is learnt in educational centres across Africa as learners’ lived experiences in their socio-cultural environments are not contextualised to enhance the relatability of the subjects of their learning. Decolonisation efforts must address exclusion and alienation and promote inclusion and epistemic agency. This paper captures various strategies to achieve these in the continent, as well as some opportunities and challenges. It maintains that multidimensional approaches to decolonisation are required to promote African-centred climate change and environment education. This includes the interrogation of existing theories and depictions of subjugation of ILK, as well as seeking ways to halt or mitigate the prevalence of ongoing epistemic exclusion in different educational contexts and locations. It also requires policymakers and education managers to commit to developing epistemically inclusive education policies, curricula, and learning frameworks that highlight the significance of place-based knowledge.